Phylogenetic Analysis Of Pigmented Marine Derived Yeast Associated With Sargassum sp. Based On Internal Transcribed Spacer (ITS) - Tri Lunggani, Arina; Kusdiyantini, Endang (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Karimunjawa Jepara is a region with high diversity, including the diversity of seaweed. Brown seaweed is potential marine organisms due to their ability to produce enzymes, pigments, and bioactive compounds. This ability makes brown seaweed one of the potential biological agents from the marine to be developed in the industrial field. However, most of these substances may not be produced by seaweed itself, but cooperation with microbes or even by bacteria or symbiotic fungi. Secondary metabolites which are pharmaceutical, enzyme, and cosmetic sources can be produced by microbial associan. The purpose of this study was to carry out phylogenetic analysis and morphological characterization of colonies from pigmented yeast associated with Sargassum sp. The results of the phylogenetic analysis indicate that isolates of KY 3 have 100% relative similarity with Cystobasidium oligophagum.